1994
DOI: 10.1016/0735-1097(94)90864-8
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of development of acute global left ventricular dysfunction in human immunodeficiency virus infection

Abstract: Although infrequent, acute global left ventricular dysfunction is not rare in the course of HIV infection. It seems to occur exclusively during the AIDS stage. Acute global left ventricular dysfunction is often fatal but may be reversible and is mainly associated with the pathologic findings of acute myocarditis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 34 publications
1
29
0
2
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12] Abnormally high levels of coagulation markers, endothelial activation markers, and platelet activation markers have also been documented in HIV-infected patients. [13][14][15] The SMART (Strategies for Management of AntiRetroviral Therapy) study confirmed that a mild-to-moderate hypercoagulable state exists in HIV infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8][9][10][11][12] Abnormally high levels of coagulation markers, endothelial activation markers, and platelet activation markers have also been documented in HIV-infected patients. [13][14][15] The SMART (Strategies for Management of AntiRetroviral Therapy) study confirmed that a mild-to-moderate hypercoagulable state exists in HIV infection.…”
Section: Introductionmentioning
confidence: 99%
“…We routinely checked for pathology similar to that seen in HIV-infected patients, including renal TMA, arteriopathy, myocardial hypertrophy and fibrosis, atherosclerosis (ATS), infarction, and myocarditis. [4][5][6][7][8][9][10][11][12] Four-micron paraffin sections were stained with H&E for routine histopathology diagnosis and with Masson trichrome for collagen detection.Immunohistochemical staining was performed on the formalin-fixed, paraffin-embedded tissues using an avidin-biotin complex HRP technique (Vectastain Elite ABC kit; Vector Laboratories) and a rabbit polyclonal antifibrinogen Ab (DAKO) as a primary Ab. …”
mentioning
confidence: 99%
“…One consequence of the increased survival is the emergence of new manifestations of HIV infection, including cardiac dysfunction. [1][2][3][4][5][6][7] Dilated cardiomyopathy and associated symptoms of congestive heart failure are being recognized with increasing frequency, with estimates that 10% to 18% of HIV seropositive individuals will manifest evidence of left ventricular dysfunction giving rise to 21 000 to 40 000 new cases of symptomatic heart failure each year by the year 2000. Despite this clinical recognition, the pathogenesis of HIV cardiomyopathy remains unclear, limiting application of both specific treatments and preventive strategies.…”
mentioning
confidence: 99%
“…In addition, echocardiography may distinguish between fulminant and acute myocarditis by identifying near-normal left ventricular diastolic dimensions and increased septal thickness in fulminant myocarditis (versus increased left ventricular diastolic dimensions and normal septal thickness in acute myocarditis), with marked improvement in systolic function in time [Tang et al, 2009]. De Castro et al, in 1994 performed a study of 136 HIV-infected patients without clinical, electrocardiographic or echocardiographic evidence of cardiovascular dysfunction on admission who were prospectively studied with serial echocardiograms; 93 of these patients had AIDS. During a mean follow-up period of 415 days, seven patients, all in the AIDS subgroup, developed clinical and echocardiographic findings of acute global left ventricular dysfunction; six of these seven patients died of congestive heart failure.…”
Section: Non-invasive Techniquesmentioning
confidence: 99%